Exploring The Future of Early Childhood Education : Research Trends and Implementation of Augmented Reality - Citariani, Ni Maede; Agustini, Ketut; Sudhata, Gde Wawan; Suartama, Kadek; Sudarma, Komang (Jurnal Paedagogy, 2025)
This study aims to examine the research trends and implementation of Augmented Reality (AR) technology in improving various aspects of child development, the challenges of its implementation, and the direction of future research in the context of digital education for early childhood. This study uses the Systematic Literature Review (SLR) method, with a bibliometric mapping approach and content analysis. A total of 17 articles were selected from the Scopus and DOAJ database in the period 2019–2024 for further analysis. The research findings show that the use of AR significantly enhances the learning experience to be more interactive, contextual, and enjoyable for children. In addition, AR has proven effective in conveying abstract concepts visually and helping to reinforce practical values such as financial responsibility from an early age. However, challenges such as limited infrastructure, access to technology, uneven teacher training, and excessive dependence on technology are major obstacles to the widespread implementation of AR. The implications of this study highlight the importance of increasing technological support in educational institutions, developing AR applications that are aligned with the curriculum, and continuous teacher training. Thus, AR has great potential as an innovative medium in early childhood education, as long as it is balanced with the right implementation strategy.